Da crítica imanente à crítica do sofrimento: a justificação normativa na obra tardia de Adorno - Fleck, Amaro de Oliveira (2016)
Adorno's critical theory is often accused of having a normative deficit, that is, it can not give an account about the criteria that it uses to criticize society. This paper aims to show, mainly by analyzing the work Negative Dialectics, as Adorno justifies his criticism. Therefore, it is necessary to investigate the idea of immanent critique and differentiate their instrumental and non-instrumental use, as well as its negative and positive use. I argue that Adorno does a purely instrumental use of positive immanent critique (a critique of ideology), while making use, ultimately, a negative immanent critique, which can be identified in his work with the critical of social suffering